1995
DOI: 10.1152/ajpgi.1995.268.1.g82
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin and carbachol require cAMP to elicit aminopyrine accumulation in isolated pig and rat parietal cells

Abstract: The role of endogenous adenosine 3',5'-cyclic monophosphate (cAMP) in the mechanisms of action of gastrin and carbachol on aminopyrine accumulation in isolated pig and rat parietal cells was investigated. In pig cells, pentagastrin (100 nM) alone stimulated aminopyrine accumulation, an action significantly reduced by the protein kinase A inhibitor Rp-adenosine 3',5'-cyclic monophosphothioate (Rp-cAMP[S]; 100 microM). In rat cells, gastrin-17 (100 nM) was incapable of stimulating aminopyrine accumulation, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…The potentiation has been thought to reflect interaction of the intracellular signal transduction pathways including the histaminergic cAMP cascade and gastrinergic/cholinergic Ca 2+ -dependent pathway. In vitro studies have demonstrated that a certain level of cAMP in parietal cells may be required for an optimal secretory response to the Ca 2+ -dependent pathway (8,9). Contrary to the above notion, the present finding that cholinergic signaling could normally control the acid secretion in H2R -/-mice indicates that the Ca 2+ -dependent pathway alone can evoke acid secretion without potentiating the H2R-mediated cAMP pathway.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The potentiation has been thought to reflect interaction of the intracellular signal transduction pathways including the histaminergic cAMP cascade and gastrinergic/cholinergic Ca 2+ -dependent pathway. In vitro studies have demonstrated that a certain level of cAMP in parietal cells may be required for an optimal secretory response to the Ca 2+ -dependent pathway (8,9). Contrary to the above notion, the present finding that cholinergic signaling could normally control the acid secretion in H2R -/-mice indicates that the Ca 2+ -dependent pathway alone can evoke acid secretion without potentiating the H2R-mediated cAMP pathway.…”
Section: Discussioncontrasting
confidence: 84%
“…Taken together with our present data, this leads us to propose that the muscarinic signal functions stimulate acid production, whereas the gastrin signal mainly functions to promote the proliferation of parietal cells. However, it has been reported that gastrin can directly stimulate isolated canine and porcine parietal cells on acid secretion (6)(7)(8). It is so far unclear why exogenously added gastrin could not induce acid secretion in the mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Because H 2 -receptor antagonists inhibit vagus nerve-and gastrin-stimulated gastric secretion, histamine is thought to represent the final mediator of acid secretion (Grossman and Konturek, 1974). In contrast, in vitro studies have demonstrated that both carbachol and gastrin directly stimulate isolated parietal cells to result in acid secretion (Soll, 1980;Pfeiffer et al, 1990;Li et al, 1995). In addition, histamine amplifies parietal cell stimulation by carbachol and gastrin.…”
mentioning
confidence: 97%
“…2+ ] i has been shown to be necessary for the cytological transformation in parietal cells and subsequent gastric acid secretion [7]. However, it was previously observed that an increase in [Ca 2+ ] i alone was not sufficient to induce full parietal cell stimulation and a simultaneous elevation in cAMP was required in order to ensure cellular stimulation [7,20]. Accordingly, we have observed that upon an increase in [Ca 2+ ] i in resting human parietal cells, a redistribution of F-actin and H + /K + -ATPase occurred.…”
Section: Discussionmentioning
confidence: 99%